THE EFFECTIVENESS OF CAPITAL ON COOPERATIVE SUSTAINABILITY: A PRISMA-BASED LITERATURE REVIEW - Apriliani, Winda; Nayla, Siti Najwa; Tarigan, Syahra Arihta Saodes; Nuriansyah, Fazar (LPPM STIE EKA PRASETYA, 2025)
Cooperatives play a significant role in improving the economic well-being of their members. However, limited access to capital often hinders their growth and sustainability. This study aims to identify an optimal capital model for ensuring cooperative sustainability. The research employs a Systematic Literature Review (SLR) using the PRISMA approach to identify, review, and evaluate studies related to cooperative capital. Data were collected from indexed scientific articles published in the last five years. The findings indicate that various capital sources—such as internal capital, working capital, equity capital, loans from financial institutions, and external partnerships—are crucial for cooperative sustainability. Furthermore, effective capital management and supportive policies can enhance efficiency and long-term viability. This study concludes that cooperatives must adopt innovative and flexible capital strategies to sustain their operations. The recommendations provided can serve as guidelines for cooperative managers and policymakers in formulating strategies that support cooperative growth in the future.